2021
DOI: 10.1007/s00167-020-06373-y
|View full text |Cite
|
Sign up to set email alerts
|

Micro-fragmentation is a valid alternative to cell expansion and enzymatic digestion of adipose tissue for the treatment of knee osteoarthritis: a comparative preclinical study

Abstract: Purpose The aim of this study was to compare three procedures to exploit adipose-derived cells for the treatment of osteoarthritis (OA) in a preclinical model, to understand their therapeutic potential and identify the most suitable approach for the clinical application. Methods Biological samples from adipose tissue, processed by mechanical micro-fragmentation (MF), enzymatic digestion (SVF) or cell expansion (ADSCs), were irst characterized in vitro and then used in vivo in a surgically induced OA rabbit mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 39 publications
(49 reference statements)
0
24
0
Order By: Relevance
“…The current study clarified some aspects of AT behaviour ex vivo and demonstrated that better preserved AT features are obtained using microfragmentation rather than centrifugation during ex vivo manipulation. A positive outcome in osteoarthritis treatment has been reported [ 10 , 11 , 38 ] MF-AT had surprisingly higher HOXB7 and bFGF expression in a pathologic SF environment, suggesting that these features are possible players in the beneficial impact on joint homeostasis. To investigate which AT processing method better preserves AT histology and performance and promotes regenerative mechanisms, two different methods (MF vs. C) were compared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study clarified some aspects of AT behaviour ex vivo and demonstrated that better preserved AT features are obtained using microfragmentation rather than centrifugation during ex vivo manipulation. A positive outcome in osteoarthritis treatment has been reported [ 10 , 11 , 38 ] MF-AT had surprisingly higher HOXB7 and bFGF expression in a pathologic SF environment, suggesting that these features are possible players in the beneficial impact on joint homeostasis. To investigate which AT processing method better preserves AT histology and performance and promotes regenerative mechanisms, two different methods (MF vs. C) were compared.…”
Section: Discussionmentioning
confidence: 99%
“…Several evidences report a significant positive clinical outcome such us in plastic surgery in the treatment of ulcers, burns, scars, soft tissue augmentation [ 5 , 7 9 ]. The application of AT-MSC was not confined to plastic surgery but was also extended to cardiac, rheumatoid, gastro-intestinal and musco-skeletal fields, etc [ 10 12 ]. For this reason, different enzymatic and mechanical procedures have been established for processing AT to isolate cells that can be locally implanted [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, MFAT was demonstrated to support cell viability, proliferation, and extracellular matrix deposition, as well as to reduce the markers of inflammation and matrix degradation in several cell types, including cartilage cells and synoviocytes [ 24 ]. In vivo, MFAT was able to improve cartilage defects repair [ 25 ], and to exert a chondro-protective action in a rabbit model of OA [ 26 ]. The mechanism of these actions depends on paracrine effectors, such as soluble molecules or extracellular vesicles that are released by the cells contained in MFAT, and that have been identified as mediators with anti-inflammatory and pro-regenerative properties [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of using MSCs from bone marrow and other tissue sites, based on their ability to influence and regulate different stages of tissue repair, is a great challenge among clinicians [ 51 , 52 ]. MSCs can be present as expanded cells, following tissue collection and isolation, or as a heterogeneous population after concentration processes with different devices [ 53 , 54 , 55 , 56 ]. Expanded MSCs and concentrated progenitors undergo different regulatory compliance, as the first approach foresees cell manipulation in GMP facilities and two-step procedures, whereas the second one requires minimal manipulation and occurs through a one-step procedure directly in the operating room [ 57 ].…”
Section: Osteoarthritis: Catabolic and Inflammatory Mechanisms And Therapeutic Modalitiesmentioning
confidence: 99%